2019
DOI: 10.1002/ps.5664
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of thrips suppression by Cry51Aa2.834_16 Bt toxin expressed in cotton

Abstract: BACKGROUND Genetically engineered (GE) crops that express insecticidal traits have improved the sustainability of insect pest management worldwide, but many important pest orders are not controlled by commercially available toxins. Development of the first transgenic thysanopteran‐ and hemipteran‐active Bacillus thuringiensis (Bt) Cry51Aa2.834_16 toxin expressed in MON 88702 cotton will significantly expand the diversity of pests controlled in the crop. Here, we examined MON 88702 cotton activity against two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…However, the mechanism of MON 88702 activity creates added challenges to resistance management in the field. Specifically, recent studies have shown that MON 88702 acts by a non-lethal antixenosis leading to suppressed oviposition that results in fewer F. fusca larvae developing on MON 88702 cotton [13][14][15][16]. Similar non-lethal suppression of oviposition by adult F. fusca in conjunction with acute larval toxicity have been documented for neonicotinoid seed treated (NST) cotton [17][18][19].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, the mechanism of MON 88702 activity creates added challenges to resistance management in the field. Specifically, recent studies have shown that MON 88702 acts by a non-lethal antixenosis leading to suppressed oviposition that results in fewer F. fusca larvae developing on MON 88702 cotton [13][14][15][16]. Similar non-lethal suppression of oviposition by adult F. fusca in conjunction with acute larval toxicity have been documented for neonicotinoid seed treated (NST) cotton [17][18][19].…”
Section: Introductionmentioning
confidence: 73%
“…Both MON 88702 cotton and neonicotinoid seed treatments have strong antixenotic effects on adult F. fusca resulting in large reductions in oviposition and larval establishment on cotton, even in the presence of alternative host plants. While MON 88702 alters feeding behavior and reduces oviposition of adults, it has minimal impacts on adult and larval survival [13][14][15][16]. Both imidacloprid and thiamethoxam applied as seed treatments also have minimal impact on survival of adult F. fusca and dramatically reduce oviposition on treated cotton seedlings; however, they also cause moderate to high levels of larval mortality [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In no-choice experiments, they oviposited less on MON 88702 than on non-Bt cotton. 10,11 A previous study of L. lineolaris feeding behavior on MON 88702 showed antifeedant activity, wherein L. lineolaris tended to spend more time engaged in pre-oral digestion activity (i.e. cell rupturing by enzymatic, macerating saliva) and exhibited shorter periods of ingestion relative to insects that fed on non-Bt cotton.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Although the spectrum of MON 88702 activity is unique, recent evidence suggests that the mechanism of population control involves a combination of lethal and non-lethal effects. 10 In choice experiments, adult female F. fusca avoided MON 88702 plants and ultimately settled and oviposited on non-Bt cotton. 9,10 In no-choice experiments, they oviposited less on MON 88702 than on non-Bt cotton.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation